Wi - Fi - based cell phone localisation - Tong, Jing Ning (2015)
Tagged is an Android application which allows users‟ location to be tracked using Wi-Fi in real time. A control station on the server side displays the locations through a map, and refreshes at regular interval to provide real-time tracking. The aim of this project is to showcase a potential method of indoor localisation using current infrastructure while keeping costs low and affordable. It is intended to allow the control station to track users easily through a single application that does not require additional input thereafter. The main aim is to introduce a viable location tracking system to manage users, using Wi-Fi. The project works by having users install an Android application into their mobile devices or tablets. Once installed, users are given a choice to register or login to use the app. For first-time users, user registration will store particulars onto the database which are then used during map identification. Subsequent usage of the app only requires a login, which will alert the database of the user‟s current online status and updates the map accordingly. The tracking starts automatically upon login, and the user may exit the app as it updates the mobile device‟s location while running in the background. On the control station side, icons will appear when the user is online and updated accordingly upon refresh. The project has met its objective of developing an indoor localisation system using Wi-Fi. A mobile phone installed with Tagged can be detected and tracked on the control system, using the current Wi-Fi infrastructure. The control system is able to display users‟ location on a map for visual representation. However, there are several points of improvements for the project to fully utilise its potential. Accuracy of the tracked location is a major concern as the current localisation method does not show locations with small marginal error. Further tests and a new calculation method may improve the current system for better tracking.